Red-backed Shrike Lanius collurio whole-genome sequencing reveals population genetic admixture - Pârâu, Liviu G.; Wang, Erjia; Wink, Michael (Diversity, 2022)
The Red-backed Shrike (Lanius collurio) is a medium-sized, carnivorous passerine, occurring throughout the western Palearctic. As with numerous other bird species, its numbers are declining, mainly due to anthropogenic factors. Therefore, revealing the population structure and genetic diversity is paramount in ensuring the survival of the species. However, until present, only mitochondrial DNA has been targeted to reveal the genetic structure of the species. These studies suggested a panmictic population structure. In this study, we employed next-generation sequencing of 88 Red-backed Shrikes from 11 countries and used single nucleotide polymorphisms (SNPs)) to investigate the population structure. Even with such high-resolution DNA data, we found considerable genetic variability, but our results indicate no genetic structure in the Red-backed Shrike, suggesting a panmictic population. Migrant birds from Israel and Kuwait could not be attributed to breeding populations. Panmixia is the genetic legacy of the widespread and continuous distribution of the species, high locomotion capacities, and, most importantly, the numerous ice ages from the past few million years, which forced various populations to retract to refugia and expand their ranges several times, and to interbreed both in the glacial refugia and during warm periods in Eurasia.